Persistent near real‐time passive acoustic monitoring for baleen whales from a moored buoy: System description and evaluation. Issue 9 (16th July 2019) - Baumgartner, Mark F.; Bonnell, Julianne; Van Parijs, Sofie M.; Corkeron, Peter J.; Hotchkin, Cara; Ball, Keenan; Pelletier, Léo‐Paul; Partan, Jim; Peters, Don; Kemp, John; Pietro, Jeff; Newhall, Kris; et al.
Abstract: Managing interactions between human activities and marine mammals often relies on an understanding of the real‐time distribution or occurrence of animals. Visual surveys typically cannot provide persistent monitoring because of expense and weather limitations, and while passive acoustic recorders can monitor continuously, the data they collect are often not accessible until the recorder is recovered. We have developed a moored passive acoustic monitoring system that provides near real‐time occurrence estimates for humpback, sei, fin and North Atlantic right whales from a single site for a year, and makes those occurrence estimates available via a publicly accessible website, email and text messages, a smartphone/tablet app and the U.S. Coast Guard's maritime domain awareness software. We evaluated this system using a buoy deployed off the coast of Massachusetts during 2015–2016 and redeployed again during 2016–2017. Near real‐time estimates of whale occurrence were compared to simultaneously collected archived audio as well as whale sightings collected near the buoy by aerial surveys. False detection rates for right, humpback and sei whales were 0% and nearly 0% for fin whales, whereas missed detection rates at daily time scales were modest (12%–42%). Missed detections were significantly associated with low calling rates for all species. We observed strong associations between right whale visual sightings and near real‐time acoustic detections over a monitoring range 30–40 km and temporal scales of 24–48 hr, suggesting that silent animals were not especially problematic for estimating occurrence of right whales in the study area. There was no association between acoustic detections and visual sightings of humpback whales. The moored buoy has been used to reduce the risk of ship strikes for right whales in a U.S. Coast Guard gunnery range, and can be applied to other mitigation applications.